2003
DOI: 10.1023/b:urol.0000020301.39181.03
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cyclin-dependent kinase inhibitor p27 in transitional cell bladder cancers: Is it a good predictor for tumor behavior?

Abstract: The results indicate that p27 is not a good predictor for outcome of transitional cell carcinoma of the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…CDKN3 is relative to hs_1‐tissue‐endocrine_and_cns, regulation of protein kinase activity, regulation of transferase activity, protein amino acid dephosphorylation, negative regulation of cell proliferation and regulation of cell proliferation (GenMAPP (http://www.genmapp.org/)). Studies into CDKN3 relationships in tumours has already been presented in a number of papers (1–13). However, distinct molecular networks and interpretation concerning CDKN3 in the cell cycle during non‐malignancy associated hepatitis/cirrhosis and hepatocellular carcinoma (HCC) transformation have remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…CDKN3 is relative to hs_1‐tissue‐endocrine_and_cns, regulation of protein kinase activity, regulation of transferase activity, protein amino acid dephosphorylation, negative regulation of cell proliferation and regulation of cell proliferation (GenMAPP (http://www.genmapp.org/)). Studies into CDKN3 relationships in tumours has already been presented in a number of papers (1–13). However, distinct molecular networks and interpretation concerning CDKN3 in the cell cycle during non‐malignancy associated hepatitis/cirrhosis and hepatocellular carcinoma (HCC) transformation have remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Doganay et al . reported high p27 kip1 immunoreactivity present in some highly aggressive bladder carcinomas 18 . High levels expression of p27 kip1 were also observed in a number of highly proliferative cancers of different organs 19–21 .…”
Section: Discussionmentioning
confidence: 93%
“…Doganay et al reported high p27 kip1 immunoreactivity present in some highly aggressive bladder carcinomas. 18 High levels expression of p27 kip1 were also observed in a number of highly proliferative cancers of different organs. [19][20][21] For example, Yatabe et al reported a higher level of p27 in small cell lung carcinomas that have a higher proliferative rate than nonsmall cell tumors.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Doganay et al, provided evidence that expression of p27 is generally low in urinary bladder carcinoma but is not related to tumor grade, stage, PCNA index, recurrence rate and prognosis. They concluded that p27 expression may not be an independent predictor of outcome with transitional cell carcinoma of the urinary bladder 31…”
Section: Discussionmentioning
confidence: 99%